PEMANFAATAN FLASHCARDS ANATOMI TUBUH MANUSIA UNTUK MENINGKATKAN PENGETAHUAN TENTANG HIPERTENSI DAN CARA PENYIMPANAN OBAT PADA SISWA SMK Al MUHADJIRIN 2 BEKASI - Bayu Dwi Handono; Pristiyantoro; Umul Angga Brahmono; Ida Diana Sari; Dwi Elsha Shanty Fauzani (Jurnal Pengabdian IKIFA, 2025)
The aim of this community service is to evaluate the effectiveness of using human anatomy flashcards and proper hypertension medication storage information as educational media to enhance students' knowledge of hypertension and medication storage. This research involved 26 respondents from SMK Al Muhadjirin 2 Bekasi who received educational intervention in the form of human anatomy flashcards and information on proper hypertension medication storage. Knowledge was measured before (pre-test) and after (post-test) the intervention using the Paired Sample t-Test. The pre-test results showed an average knowledge score of 10.27, which increased to 10.92 in the post-test, with an average difference of -0.65. Normality test using Shapiro-Wilk indicated that the pre-test data were normally distributed (p=0.253 > 0.05). The Paired Samples t-test results showed a p-value of 0.003 (p < 0.05), indicating a statistically significant difference between pre-test and post-test scores. This demonstrates that flash cards are effective in improving participants' understanding of human anatomy, its relationship with hypertension, and the importance of proper medication storage